Dysregulation of glucose metabolism since young adulthood increases the risk of cardiovascular diseases in patients with bipolar disorder - Pao-Huan Chen; Yen-Kuang Lin; Chi-Kang Chang; Shuo-Ju Chiang; Shang-Ying Tsai (Kaohsiung Journal of Medical Sciences, 2017)
Aging patients with bipolar disorder (BD) are at a high risk of cardiovascular diseases (CVDs). However, few studies have directly examined the association between metabolic risks and CVDs in patients with BD across the lifespan. Therefore, the aim of this study was to determine lifetime metabolic risk factors for CVDs in patients with BD. We recruited BD-I patients who were more than 50 years old and had had at least one psychiatric hospitalization. Patients who had a cardiologist-confirmed CVD diagnosis (ICD-9 code 401–414) were assigned to the case group. Fifty-five cases were matched with 55 control patient without CVDs based on age and sex. Clinical data were obtained by retrospectively reviewing 30 years of hospital records. Compared to control subjects, a significantly higher proportion of cases had impaired fasting glucose between ages 31 and 40 (44.0% versus 17.4%, p = 0.046), diabetes mellitus between ages 41 and 50 (25.6% versus 8.6%, p = 0.054), and diabetes mellitus after age 51 (36.3% versus 12.7%, p = 0.005). No significant difference was found in overweight, obesity, or dyslipidemia. After adjusting for years of education, first episode as mania, and second generation antipsychotic use, lifetime diabetes mellitus remained a risk factor for CVDs (OR = 4.45, 95% CI = 1.89–10.66, p = 0.001). The findings suggest that glucose dysregulation across the adult age span is probably the major metabolic risk contributing to CVDs in patients with BD. Clinicians therefore have to notice the serum fasting glucose levels of BD patients since young adulthood.